Dampak kesulitan identifikasi emosi pada anak dengan Developmental Language Disorder (DLD): Tantangan dalam interaksi sosial dan pengembangan emosional - Wardani, Hanna Mustafidah Kusuma (Maliki Interdisciplinary Journal, 2023)
The ability to identify emotions is an important component in social interaction and emotional development of children. Because to communicate we must understand the emotions of our interlocutor so that we are not wrong when interpreting what he said. However, children with Developmental Language Disorder (DLD) face difficulties recognizing and understanding emotions, which can have a negative impact on their daily lives. This article analyzes the impact of difficulties in identifying emotions in children with DLD, including difficulties in social interaction, communication disorders, difficulties in emotional regulation, and low social skills that can make them victims of bullying and even perpetrators of bullying. This research aims to create a deeper understanding of these impacts and the need for appropriate interventions to help children with DLD overcome their difficulties in identifying their emotions. As well as helping them to overcome challenges in social interaction and their emotional development.